Report of meeting Researches in Didactics of Mathematics and Computer Sciences: January 30 - February 1, 2009, Debrecen, Hungary (Teaching Mathematics and Computer Science, 2009)
The meeting Researches in Didactics of Mathematics and Computer Sciences was held in Debrecen, Hungary from January 30 to February 1, 2009. The 49 Hungarian participants – including 15 PhD students – came from 18 cities and represented 29 institutions of higher education. The abstracts of the talks and the posters and also the list of participants are presented in this report.